2001
DOI: 10.1007/s004300100073
|View full text |Cite
|
Sign up to set email alerts
|

Post transcriptional control of gene expression in Leishmania

Abstract: Leishmania parasites are ancient eukaryotes, characterized by unusual molecular mechanisms. We have used the gene encoding for Hsp83 as a model system for studying regulatory mechanisms that control developmental gene regulation. We previously showed that protein coding genes are regulated exclusively by post-transcriptional mechanisms, while no transcriptional activation could be observed even for the conserved Hsp83 gene. We now show that processing and maturation of the Hsp83 polycistronic primary transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…However, such an approach is not feasible for Hsp90 or Hsp70 since both proteins are encoded by multiple, tandemly arranged, identical gene copies in Leishmania spp. (Lee et al ., ; Hubel and Clos, ; Shapira et al ., ). So far, no tandem arrays of genes have been successfully targeted for replacement in Leishmania spp.…”
Section: Discussionmentioning
confidence: 97%
“…However, such an approach is not feasible for Hsp90 or Hsp70 since both proteins are encoded by multiple, tandemly arranged, identical gene copies in Leishmania spp. (Lee et al ., ; Hubel and Clos, ; Shapira et al ., ). So far, no tandem arrays of genes have been successfully targeted for replacement in Leishmania spp.…”
Section: Discussionmentioning
confidence: 97%
“…Although, the size difference between these transcripts could not be explained by the sole difference in size of both 3' UTRs, it is likely that the differences are due to different length of the poly(A) tail [42,43]. Noticeably, it is considered that unstable mRNAs carry shorter poly (A) tails [44,45]. Northern blot assays showed that the steady-state levels of both transcripts are not affected by the temperature of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…During infection, Leishmania promastigotes mount a heat stress response to elevated temperatures encountered following inoculation from the sandfly into the mammalian host. Such stress responses typically result in a generalized decrease in protein synthesis (Hunter et al, 1984;Shapira et al, 1988;Zilberstein and Shapira, 1994), albeit with an induction of specific proteins, such as heat shock proteins (Shapira et al, 2001). Significantly, this heat stress alone represents the primary physiologic signal for amastigote development (Zilberstein and Shapira, 1994;Alcolea et al, 2010), suggesting a link between heat stress and translational control in amastigote differentiation.…”
Section: Introductionmentioning
confidence: 99%